2004
DOI: 10.1038/nri1489
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral restriction by APOBEC proteins

Abstract: A powerful mechanism of vertebrate innate immunity has been discovered in the past year, in which APOBEC proteins inhibit retroviruses by deaminating cytosine residues in nascent retroviral cDNA. To thwart this cellular defence, HIV encodes Vif, a small protein that mediates APOBEC degradation. Therefore, the balance between APOBECs and Vif might be a crucial determinant of the outcome of retroviral infection. Vertebrates have up to 11 different APOBEC proteins, with primates having the most. APOBEC proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
540
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 582 publications
(557 citation statements)
references
References 104 publications
11
540
0
6
Order By: Relevance
“…The human apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like (APOBEC) gene family comprises 11 genes: the Activation-Induced Cytidine Deaminase (AICDA), APOBEC1 (A1) and seven A3s encode (deoxy)cytidine deaminases capable of targeting RNA and/or DNA; A2 does not appear to posses catalytic activity and A4 remains uncharacterized [1]. The founding member, A1 was cloned over 20 years ago and shown to be responsible for the deamination (see Glossary) of cytidine 6666 in the ApoB mRNA, converting it to uridine and generating a stop codon that creates a shorter ApoB 48 protein [2,3].…”
Section: Deoxycytidine Deamination In Innate Immunity and Somatic Mutmentioning
confidence: 99%
“…The human apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like (APOBEC) gene family comprises 11 genes: the Activation-Induced Cytidine Deaminase (AICDA), APOBEC1 (A1) and seven A3s encode (deoxy)cytidine deaminases capable of targeting RNA and/or DNA; A2 does not appear to posses catalytic activity and A4 remains uncharacterized [1]. The founding member, A1 was cloned over 20 years ago and shown to be responsible for the deamination (see Glossary) of cytidine 6666 in the ApoB mRNA, converting it to uridine and generating a stop codon that creates a shorter ApoB 48 protein [2,3].…”
Section: Deoxycytidine Deamination In Innate Immunity and Somatic Mutmentioning
confidence: 99%
“…24 APOBEC3 proteins constitute a powerful mechanism of vertebrate innate immunity by providing intracellular resistance to retrovirus replication. 25 Human APOBEC3A has the ability to enter the nucleus and shows specificity for singlestranded DNA. The inhibition of AAV by hA3A is the first example of an APOBEC protein that targets a virus that replicates exclusively in the nucleus without passing through an RNA intermediate.…”
Section: Innate Immunitymentioning
confidence: 99%
“…These classes of restriction factors are considered below but more detailed reviews are found elsewhere. 30,[73][74][75] Interferons are also well established to perturb early retroviral infection, lowering proviral DNA, [76][77][78][79] but are not discussed here due to space constraints.…”
Section: Avoiding Host Cell Restrictionsmentioning
confidence: 99%
“…80 Since this seminal study, multiple human APOBEC3 family members and their homologues in other species are reported to block diverse retroviruses (reviewed in Harris and Liddament 75 ). The APOBEC3 proteins belong to an enzyme family that all deaminate cytidine (C) bases to uracil (U) in DNA or RNA.…”
Section: Avoiding Host Cell Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation